Bi-axial testing of composite laminates and adhesive bonded joints - Nguyen, Hai Dang (2018)
Glass/carbon fiber-reinforced polymer matrix composite shell/laminates have been increasingly employed in wind power industry to fabricate lightweight and stiff blades. These anisotropic materials are used in the wind turbine blades subjected complex stress states. By using data from a conventional uniaxial test of the composite laminate in the design processes, safety factors might be overestimated which might lead to unnecessary enlargement of structure sizes. To achieve more realistic loading conditions, bi-axial tests have been conducted in recent studies. However, there is still a lack of reliable biaxial testing data for composite materials because of the difficulties and expense of conducting these tests. The aim of this study is to investigate the failure behavior of fiber reinforced polymer matrix composite laminates and adhesively bonded joints under in-plane bi-axial loading conditions. Firstly, a novel bi-axial testing fixture which can produce the tension – tension, tension – compression, compression – compression bi-axial loading conditions with different displacement ratios was developed using cruciform specimens. This can be a low-cost alternate to characterize the behaviors of composite laminates under in-plane bi-axial stress states. Secondly, fracture characteristics of unidirectional and cross-ply glass FRP composite laminates were investigated under bi-axial tension – shear loading conditions using a modified Arcan fixture. Different crack propagation patterns were observed in these tests. The cross-ply specimens under tensile stress failed from the crack tips in a sudden catastrophic manner while the fracture of these specimens under shear stress occurred gradually in the direction which was perpendicular to the crack orientation. The unidirectional specimens failed in the direction which parallels to the fiber direction in all test cases Moreover, the fracture toughness values were determined and plotted in a fracture toughness space. Fracture toughness of glass fiber-reinforced polymer composite materials depends on the lay-up sequence. With the same number of plies, the cross-ply laminates had greater fracture toughness than the laminates. Besides, the opening mode fracture toughness was much higher than the shearing mode result. These findings offer a better understanding of crack initiation and propagation mechanisms of FRP composite laminates under biaxial tension – shear loading conditions. The experimental data are useful to verify the failure theories for composite materials. Thirdly, the failure behaviors of cross-ply laminate cruciform specimens were studied under the in-plane bi-axial tension – tension and tension – compression bi-axial static loading condition using cruciform specimens. These tests provide a reliable data for composite structure designs as numerical of composite products and structure are mostly flat or gently curved. The results were generated under axial – transverse critical stress surface and fracture toughness surface. For pure mode I tests, the tensile transverse stress produced closure crack effect and compressive transverse stress induced opening crack behavior. Moreover, the material becomes notch – insensitive when the tensile transverse stress is much higher than axial tensile stress. For the mixed-mode tests, the mode I dominant behavior is observed in the fracture toughness space for most tests. This finding is verified by investigation of the crack paths and crack patterns during the tests which are typical for mode I failure. This means the opening crack mode is the most important mode for the laminate with cracks under bi-axial loading conditions. For tension – compression tests, the specimens had failed in different ways depending on the stress ratio. The cracks propagate from crack tips then generate the mode I fracture under the low transverse stress. However, at higher compressive transverse stress, a compressive failure with a shear band is visible for the bi-axial tests. Therefore, numerical failure scenarios can occur together during the bi-axial tests which are different from uniaxial tests. These realistic behaviors are significant to the composite community to enhance material efficiency in composite designs. Finally, the influence of the contours of adhesively bonded surfaces to the strength of adhesively bonded joints under bi-axial tension – shear loads was experimental and numerical investigated. Three different types of specimens with the straight, rectangle shape and triangle shape contours were used in the experiment using a modified Arcan fixtures. Furthermore, three-dimensional finite element models were developed to predict the strength of the adhesively bonded joints as well as inspect the stress distribution in the adhesive layers. The experimental results obtained show that the straight contour specimens give the highest strength for all combination of tension and shear loads. Nevertheless, the numerical results show the different trend as the straight contour specimens has the weakest strength among three types of specimens. Considering the influence of the stress concentration, the stress distributions in the adhesive layers of rectangle and triangle shape contour specimens express a high level of stress concentration which induced the nonlinear behaviors of adhesive materials. This results in a need for a nonlinear model which can simulate the performance of adhesive layer after the yield point. However, the current models can predict the strength of straight contour specimens in good agreement with the experimental measurements.